The effect of pressurized induced flow on downdraft gasifier performance with low emission burner - 302692 Lukeman Yusoff (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2004